Comparative study of efficacy of intradermal tranexamic acid microinjections versus intradermal glutathione microinjections for treatment of facial melasma - Kanchan Kumawat; Kailash Bhatia; Jushya Bhatia; Rajesh Kataria; Chaitanya Namdeo; Ankur Sarin (Wolters Kluwer Medknow Publications, 2022)
Background Melasma is a hypermelanotic disorder, which poses therapeutic challenge. Tranexamic acid (TA) and glutathione are novel therapies for the treatment of melasma. Aim To compare the therapeutic efficacy of localized intradermal microinjections (mesotherapy) of TA versus microinjections of glutathione for the treatment of melasma. Methods This prospective, comparative study was carried out to assess the therapeutic efficacy of TA and glutathione in 64 patients with dermal melasma after obtaining written informed consent, over a period of 12 weeks. Face of the patient was divided into two halves (split face); right cheek was injected with TA and the left with glutathione, at baseline (zero), 4th, 8th, and 12th weeks. The treatment response was assessed by using visual analog scale (VAS); photographs were taken to ascertain the improvement and its percentage was calculated. A parametric test, Student t test, and Z test were applied wherever applicable. P-value of <0.05 was considered statistically significant. Results Out of 64 enrolled, 50 patients completed the study and it was found that the reduction in VAS score from baseline to 8th week and baseline to 12th week was significant in both the groups (P < 0.05). However, the mean difference in improvement percentage between baseline and 8th week and baseline and 12th week with TA was found to be more significant than glutathione. Conclusion This study revealed that both TA and glutathione intradermal microinjections are effective in the treatment of melasma but TA is more effective.